Study on the structural and luminous properties of two kinds self-luminous fibers. Issue 3 (3rd March 2020) - Pang, Zengyuan; Zhu, Yanan; Ge, Mingqiao
Abstract: Reports on the structural and optical characteristics of rare earth luminous fibers have been launched, two kinds of red light emitting luminous fibers: SrAl2 O4 :Eu 2+, Dy 3+ /light conversion agent-PET as well as SrAl2 O4 :Eu 2+, Dy 3+ -light conversion agent-PET were artificially manufactured, using rare-earth strontium aluminate SrAl2 O4 :Eu 2+, Dy 3+ as the rare-earth luminescent material. Their luminous properties depended on Eu 2+, Dy 3+ and fiber-forming polymers, with dispersion agent as a matrix. Herein, studies related to emitting red light of this two kinds of luminous fibers have been widely carried out. The morphology and EDS as well as luminous properties of the resulting samples were characterized. The results showed that the emission spectrum had a broad band from 450 to 590 nm with the two highest excitation intensity located at 520 and 580 nm for SrAl2 O4 :Eu 2+, Dy 3+ -light conversion agent-PET, and at 520 and 605 nm for SrAl2 O4 :Eu 2+, Dy 3+ /light conversion agent-PET. The brightness and the afterglow time of SrAl2 O4 :Eu 2+, Dy 3+ -light conversion agent-PET were lower than that of SrAl2 O4 :Eu 2+, Dy 3+ /light conversion agent-PET.